Synchronizing Leadership and Culture: A Roadmap for Organizational Success in the Disruptive Age - Adivi, Venkat (Digital Repository of Theses, 2024)
The onset of the digital age has brought with it an unprecedented wave of disruptions, compelling organizations to rethink traditional approaches to leadership and culture. This thesis explores the symbiotic relationship between organizational culture and leadership, laying down a comprehensive roadmap for synchronizing these critical elements to navigate the complexities of the disruptive landscape. Utilizing a mix of qualitative and quantitative research methods, including literature review, case studies, and survey-based data collection, the study offers empirical insights into how mid-level management serves as crucial culture carriers and implementors of abstract strategic concepts. The research also examines the transformative power of culture-driven leadership in diverse contexts, focusing on its role in enhancing organizational performance metrics. Recommendations for practitioners and future researchers have been provided, suggesting ways to implement culture-centric leadership at various organizational stages and across diverse industries. Key case studies like Nadella's transformation of Microsoft and concepts like Mythopoetic Leadership have been cited to offer real-world examples of successful implementation of this approach. The thesis makes a compelling argument for a self-sustaining culture shaped by aligned leadership as the cornerstone for ensuring organizational readiness and resilience in a disruptive age.